The Relationship Between Cadre Participation with The Use of Long-Term Contraception Methods in Adulthood in The Banjeng Maguwoharjo Posyandu Area Sleman Yogyakarta - Puspito Panggih Rahayu; Casnuri Casnuri (Jurnal Kebidanan, 2023)
Background: Long-term contraceptive methods are effective methods for delaying and spacing pregnancies, as well as stopping fertility. Therefore, the government is trying to increase the use of long-term contraceptives, but the use of non-long-term contraceptives is more than the use of long-term contraceptives. Objective: The study aimed to determine the relationship between the participation of health cadres in providing information regarding long-term contraceptive methods on the use of long-term contraceptives by WUS in the Banjeng Maguwoharjo Posyandu area, Depok, Sleman, Yogyakarta. Method: This research method is descriptive correlative using a cross-sectional design. The population and sample are WUS in Banjeng Hamlet, consisting of 25 people. The variables studied were the role of cadres and the use of long-term contraceptive methods. Univariate and bivariate data were analyzed using the chi-square test. The research data is primary data and secondary data with a questionnaire research instrument. Primary data was collected by distributing questionnaires and in-depth interviews to WUS. Result: The results showed that there was no relationship between the participation of cadres and the use of long-term contraceptive methods. This is evidenced by the p-value of 0.08. Conclusion: There is no relationship between the participation of cadres and the use of long-term contraceptive methods.